CFD simulation of the GALLOP system designed for horizontal gas well deliquifaction (2017)
This paper shows the study of a new artificial lift system, known as GALLOP, for horizontal gas well deliquifaction using CFD software. To begin with, the casing is filled with water coming from the reservoir due to changes in the inner pressure causing the valves to open. Afterwards, gas is injected in the double pipe system in order to expel the water accumulated. For the simulations there were three conditions of gas injection considered and the system was initially assumed to be completely full of water. A low, a mid, and high gas injection were included, being 30, 50 and 70 CFM, respectively. Additionally, the valves on the mandrel were simulated both as open or closed. The simulations were conducted using STAR-CCM+ v12.02 software with a VOF model (Volume of Fluid model). Also, due to computational cost and results quality, a normal mesh was implemented. All simulations showed that the gas was able to travel all the way through the system but did not expel the water completely, mainly because of gravitational force and the extended height of the vertical pipe. As it was expected, the highest injection rate was able to reach the vertical outlet first and thus had the most stable void fraction. Likewise, it was clear that the void fraction was more stable when the valves were closed, indicating that the liquid was removed successfully. Additionally, all of the injection rates showed a clear annular pattern in the horizontal piping. On the other hand, the pressure drop for an injection of 30 CFM with closed valve was compared to experimental data showing an error of 34.4 %, where more experimental data must be conducted, a finer mesh, and more specialized mathematical model must be implemented to achieve more accurate results. Lastly, the other two conditions were compared using the non-slip model since there is no experimental data yet available